2002
DOI: 10.1074/jbc.m110614200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Second Extracellular Loop (E2) of the Neurokinin-1 Receptor in the Binding of Substance P

Abstract: Substance P (SP) interacts with the neurokinin-1 (NK-1) G-protein-coupled receptor, which has been cloned in several species. In the present study, the domains of the NK-1 receptor involved in the binding of SP and SP-(7-11) C-terminal fragment have been analyzed using two peptide analogs containing the photoreactive amino acid para-benzoylphenylalanine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…Many photoaffinity crosslinking reports (including studies from us and others working on different ligand-receptor systems) which identified methionine as the crosslinked residue [1,3,15,16], may now warrant interpretation in a new light. The identified sites of interaction might have been significantly shifted by the presence of methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Many photoaffinity crosslinking reports (including studies from us and others working on different ligand-receptor systems) which identified methionine as the crosslinked residue [1,3,15,16], may now warrant interpretation in a new light. The identified sites of interaction might have been significantly shifted by the presence of methionine.…”
Section: Discussionmentioning
confidence: 99%
“…1) is critical for NK1-SP interaction (33). Furthermore, the two loop residues Met-174(C-6) and Met-181(Cϩ1) are close to the ligand in NK1-SP complexes (15,17,19,21). Specifically, the conserved disulfide bridge positions Met-181(Cϩ1) approximately one helical turn above His-108 (colored green in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the substitution of Phe-8 of SP, SP(BzF8), resulted in cross-linking to Met-181(Cϩ1) and possibly Met-174(C-6) (highlighted in red, Fig. 1A) (15,17,19,21). Taken together, the previous ligand binding studies indicated that the SP peptide presumably interacts with epitopes presented on the outer part of the extracellular portion of the NK1 receptor, but the overall results have not led to a satisfactory refined model of how SP binds to the NK1 receptor.…”
Section: Substance P (Sp) Is a Neuropeptide That Mediates Numerous Phmentioning
confidence: 99%
See 2 more Smart Citations